Three new species of the family Pennellidae (Copepoda: Siphonostomatoida) from gobiid fishes (Actinopterygii: Perciformes) in coastal waters of the western Pacific Ocean - Uyeno, Daisuke; Nagasawa, Kazuya (Zootaxa, 2010)
Three new species of pennellid copepods are described based on specimens taken from gobiid fishes. Creopelates nohmijimensis n. sp. was found on Priolepis boreus (Snyder) in the Seto Inland Sea, Japan. This new species is distinguishable from its sole congener, C. floridus Shiino, 1958, by the presence of four finely digitate lobes on the cephalothorax and in having four pairs of legs occurring closely together at the anterior end of the neck. Two new species of Cardiodectes, C. asper n. sp. and C. bertrandi n. sp., were collected, from Trimma grammistes (Tomiyama) off IzuOshima Island, Japan and Eviota sp. off the Loyalty Islands, New Caledonia, respectively. Cardiodectes asper n. sp. is distinguished from its 12 congeners by the absence of the abdomen, byhaving a trunk not longer than twice of its width, a cephalothorax with three pairs of lateral lobes, and a pair of neck lobes carrying leg 3 on the posterior surface of their bases. Cardiodectes bertrandi n. sp. is identifiable by the presence of two pairs of lateral cephalothoracic lobes, with smaller anterior pairs; a trunk twice as long as wide; and leg 3 located at the posterior end of the anterior neck lobe.